Toxicity of Necrostatin-1 in Parkinson's Disease Models - Eva Alegre-Cortés; Alicia Muriel-González; Saray Canales-Cortés; Elisabet Uribe-Carretero; Guadalupe Martínez-Chacón; Ana Aiastui; Adolfo López de Munain; Mireia Niso-Santano; Rosa A. Gonzalez-Polo; José M. Fuentes; Sokhna M. S. Yakhine-Diop (MDPI AG, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder that is characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta. This neuronal loss, inherent to age, is related to exposure to environmental toxins and/or a genetic predisposition. PD-induced cell death has been studied thoroughly, but its characterization remains elusive. To date, several types of cell death, including apoptosis, autophagy-induced cell death, and necrosis, have been implicated in PD progression. In this study, we evaluated necroptosis, which is a programmed type of necrosis, in primary fibroblasts from PD patients with and without the G2019S leucine-rich repeat kinase 2 (LRRK2) mutation and in rotenone-treated cells (SH-SY5Y and fibroblasts). The results showed that programmed necrosis was not activated in the cells of PD patients, but it was activated in cells exposed to rotenone. Necrostatin-1 (Nec-1), an inhibitor of the necroptosis pathway, prevented rotenone-induced necroptosis in PD models. However, Nec-1 affected mitochondrial morphology and failed to protect mitochondria against rotenone toxicity. Therefore, despite the inhibition of rotenone-mediated necroptosis, PD models were susceptible to the effects of both Nec-1 and rotenone.